Pengaruh Likuiditas, Profitabilitas dan Struktur Aktiva terhadap Struktur Modal pada Perusahaan Farmasi yang Terdaftar Di Bursa Efek Indonesia Periode 2018-2020 - Ayu Lestari, Febi; Adnan Pratama, Ifanny (LPPM STIE PPI, 2022)
Introduction/Main Objectives: To determine the effect of liquidity, profitability, asset structure on the capital structure of pharmaceutical companies listed on the Indonesia Stock Exchange (IDX). Background Problems: As a result of Covid-19 the role of the pharmaceutical sector is very important and needed so that the needs in terms of medicines consumed during treatment and recovery are very much needed, both personal requests (individuals) and agencies (Hospitals and Health Centers). Novelty: Researching pharmaceutical sector companies for a period of three years when there was an outbreak of a very dangerous virus, namely COVID-19, both in the world and especially in Indonesia, was very influential, especially for the economy in the pharmaceutical company sector. Research Methods: This type of research is descriptive quantitative approach using secondary data and analysis tools using SPSS. Finding/Results: Liquidity, profitability, asset structure on capital structure then partially profitability has no significant effect on capital structure, liquidity and asset structure have a negative and significant effect on capital structure. Conclusion: It becomes a material consideration in making investment decisions and pays more attention to the rate of return on shares as well as knowing more about obtaining financial statement information.